Análisis de la libertad de expresión en la fanpage crudo Ecuador en el 2017 - Mayeza Castro, Gilda (2020)
The right to freedom of expression is a principle of democratic society and not only a right, but currently in Ecuador this rights has been regulated by the Organic Law of Communication, which within its statutes and norms infers the Respect for people and cuts free opinion, this is the case of the Fanpage Crudo Ecuador, the same one that operated without significance until 2012 than with the publication of a meme where ex-president Eco was made a show. Rafael Correa Delgado on his double moral when saying during a Saturday that they were going to increase the taxes to the hairdressers for not preferring to consume national products, but instead imported merchandise from recognized stores and expensive brands. In view of this, there was a media persecution that ended in 2015 with the temporary closure of the Fanpage, it is precisely in view of this that in this case study freedom of opinion will be analyzed during 2017 with reference to this Fanpage and if in the Currently, there is freedom of expression or not, for which observation sheets will be used that allow the collection of information on the memes published in 2017, analyzing their narrative, the satire and the populisms used for their expression, as well as the comments issued by subscribers to this page. The results obtained in the development of the research showed that in web 2.0. There is greater freedom of opinion and expression, which is only regulated by community regulations.